Poetics of Migration Trauma in Mohsin Hamid’s "Exit West" - Liaqat, Qurratulaen (English Studies at NBU, 2022)
Migration has emerged as one of the most pertinent issues in the contemporary milieu. Currently, more than ever, people from many countries are being forced to migrate because of religious, social, cultural, national, racial and economic issues. This increasing trend of shifting from one place to another is causing an epistemological shift in the current milieu of human history. Exit West (2017) by Hamid is one of those novels that develops a discursive discourse of the ongoing migrant crisis, and highlights the ugly realities related to the phenomenon of relocation. It chronicles the story of two lovers, Nadia and Saeed, who migrate from their conflict-ridden country to save their lives. This paper configures the poetics of migration trauma in the contemporary literature by analyzing the symbols, metaphors and narrative technique used in Hamid’s text with the aim of tracing a discursive aesthetic trajectory of the migration trauma discourse.